Sustainability assessment of road infrastructure using sustainability index. Issue 1 (22nd November 2017) - Alam, Shafiq; Kumar, Arun; Dawes, Les
Abstract : Sustainable development as a concept has been evolved to manage emerging issues such as global warming, natural resource depletion and growing sociopolitical contention. It has gained momentum with the declaration of the sustainable development goals by the United Nations. Road transport is one of the principal sources of greenhouse gas (GHG) emissions and many other environmental and social concerns. Conventional road asset management systems (Rams) prioritise roadworks mainly based on life cycle economic assessment. For sustainable delivery, the life cycle environmental and social impacts need to be integrated in the process. Road environmental impact can be accounted from life cycle emission assessment of roadworks and uses, while road social impact can be assessed from life cycle positive and negative well-being factors. A new index termed 'road sustainability index' (RSI) has been proposed to deliver sustainable roadworks by integrating key indicators of the three dimensions of sustainability. It would ensure best economic value, least GHG emissions and optimised social outcome from life cycle viewpoint in a balanced way. The RSI values of road projects can be calculated using the data and tools of the conventional Rams. Effective application of RSI promises improved sustainability of road networks in the future.